Korean American families in immigrant America : how teens and parents navigate race - Okazaki, Sumie; Abelmann, Nancy (New York University Press, 2018)
"Korean American Families in Immigrant America: How Teens and Parents Navigate Race" explores the lives of Korean immigrants in the US and the ways that being a Korean immigrant in America influences relationship dynamics between parents and children of immigrants."--Provided by publisher.